2003
DOI: 10.1152/ajprenal.00249.2002
|View full text |Cite
|
Sign up to set email alerts
|

Transfection of CYP4A1 cDNA increases vascular reactivity in renal interlobar arteries

Abstract: HETE, a cytochrome P-450 4A (CYP4A1)-derived arachidonic acid metabolite, is a major eicosanoid formed in renal and extrarenal microcirculation. 20-HETE inhibits Ca 2ϩ -activated K ϩ channels in vascular smooth muscle cells and thereby may modulate vascular reactivity. We transfected renal interlobar arteries with an expression plasmid containing the cDNA of CYP4A1, the low-Km arachidonic acid -hydroxylase, and examined the consequences of increasing 20-HETE synthesis on constrictor responses to phenylephrine.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
30
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 25 publications
3
30
0
Order By: Relevance
“…The level of 20-HETE in renal interlobar arteries was reduced by treatment with DDMS, implying that vascular 20-HETE production is dependent on the activity of 1 or more CYP4A oxygenases. 2,5 CO is known to interfere with the activity of cytochrome P450 enzymes and therefore is expected to decrease 20-HETE synthesis. 9 In keeping with this notion, we found that the level of 20-HETE falls in renal interlobar arteries incubated in buffer containing exogenous CO (1 mol/L).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The level of 20-HETE in renal interlobar arteries was reduced by treatment with DDMS, implying that vascular 20-HETE production is dependent on the activity of 1 or more CYP4A oxygenases. 2,5 CO is known to interfere with the activity of cytochrome P450 enzymes and therefore is expected to decrease 20-HETE synthesis. 9 In keeping with this notion, we found that the level of 20-HETE falls in renal interlobar arteries incubated in buffer containing exogenous CO (1 mol/L).…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, we confirmed previous reports that the sensitivity of small arteries to phenylephrine and vasopressin is decreased by exogenous CO 1 and increased by exogenous 20-HETE. 2,4 The reactivity of the vessels to the constrictor agonists also is decreased and increased, respectively, by CO and 20-HETE manufactured by the renal vessels themselves because their sensitivity to phenylephrine and vasopressin was found to increase in response to HO inhibition with CrMP 1 and to decrease after CYP4A inhibition with DDMS. 2,4 Notably, neither exogenous CO nor CrMP effected changes in responsiveness to the constrictor agonist in vascular preparations undergoing CYP4A inhibition with DDMS.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations